OPTIMALISASI PERAN PENYULUH KESEHATAN EDUKASI VIDEO ANIMASI MENINGKATKAN PENGETAHUAN USIA PRODUKTIF TERHADAP RESIKO ANEMIA DI SMAN I MATARAMAN KAB. BANJAR - Sari Wahyunita; Andri Nur Rahman; Akhmad Yanie; Aulia Ramadhani (Jurnal Abdimas Bina Bangsa, 2024)
Anemia is a global health problem that affects various age groups, including the productive age. Anemia in young women has a significant impact on productivity, including affecting their ability to concentrate, learn, and actively participate in school activities. This community service activity aims to optimize the role of the health extension team by using video education media to see the level of knowledge for female students productive age for anemia prevention at SMAN 1 Mataraman, Banjar Regency. The method used is pretest and postest using google form with a total of 89 female students. The results obtained in this activity were before being given an animated video with the results of a knowledge level of 52 people 58% (medium knowledge level) and after being given an animated video 77 people, 86% (good knowledge level). With increased knowledge, female students can understand and contribute With increased knowledge, young women can understand and contribute to healthy living, healthy diets, iron supplementation, and lifestyles that support the prevention of anemia